Analisis Strategi Mengatasi Kesulitan Menghitung Kombinasi dengan Membagi pada Siswa Kelas 3 Sekolah Dasar Muhammadiyah 16 Medan - Rekhi Windana; Ahmad Calam; Dewi Purnamasari (Medan Resource Center, 2026)
Mathematics learning in elementary school plays an essential role in developing students’ logical reasoning, systematic thinking, and problem-solving skills. Nevertheless, many lower-grade students continue to experience difficulties in understanding fundamental mathematical concepts, particularly division and simple combinations. This study investigates how teachers address students’ difficulties in calculating combinations through division among second-grade students at SD Muhammadiyah 16 Medan City. Employing a qualitative descriptive approach, the research involved second-grade mathematics teachers and students as participants. Data were collected through classroom observations, semi-structured interviews, and documentation and were analyzed using the interactive model of Miles, Huberman, and Saldana with the support of NVIVO 15 software. The findings revealed that 11 students experienced significant difficulties related to understanding division as an equal-sharing process, connecting division concepts to simple combination problems, avoiding procedural errors, and translating word problems into mathematical operations. Repeated explanations emerged as the most dominant instructional strategy, complemented by gradual exercises, individual assistance, and contextual learning activities. Students demonstrated stronger conceptual understanding when instruction incorporated concrete examples and real-life situations. These findings highlight the practical importance of combining repetitive guidance with contextual and concrete learning experiences to improve mathematical comprehension and problem-solving abilities among elementary school students.